PENGARUH POLA ASUH ORANG TUA TERHADAP HASIL BELAJAR MATA PELAJARAN KEAMANAN PANGAN SISWA SEKOLAH MENENGAH KEJURUAN - Emilia Agawita; Sri Wahyu Andayani (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2021)
AbstractThe purpose of this study was to determine 1) the effect of parenting on food safety learning outcomes, 2) learning outcomes in food safety subjects, and 3) parenting styles. This research is an ex-post facto research. Methods of data collection using questionnaires and documentation. The data analysis technique used descriptive analysis techniques and hypothesis testing using the Product Moment correlation test which was preceded by a test of normality and linearity. The research shows that 1) There is an influence of parenting style on learning outcomes of food safety with the correlation coefficient rcount 0.620> 0.239. The determinant coefficient (R2) is 0.384, meaning that the amount of contribution given is 38.4%, while the remaining 61.6% is influenced by other factors not discussed in this study. 2) Parenting style is mostly in the moderate category with a relative frequency of 47.06%. 3) The learning outcomes of food safety subjects were mostly in the high category with a frequency of 86.76%.Keywords: Parenting Patterns, Learning Outcomes, Food Safety